Deep Ellum : The Other Side of Dallas - Govenar, Alan B., 1952- (Book collections on Project MUSE., 2013)
Deep Ellum, on the eastern edge of downtown Dallas, retains its character as an alternative to the city's staid image with loft apartments, art galleries, nightclubs, and tattoo shops. It first sprang up as a ramshackle business district with saloons and variety theatres and evolved, during the early decades of the twentieth century, into a place where the black and white worlds of Dallas converged. This book strips away layers of myth to illuminate the cultural milieu that spawned such seminal blues and jazz musicians as Blind Lemon Jefferson, Buster Smith, and T-Bone Walker, and that was also an incubator for the growth of western swing.